Evaluation of foliar application of Methanol effects on some morphological, physiological and biochemical indices of Lentil (Lens culinaris Medik.) under water deficit stress - Raheleh Ahmadpour; Nezam Armand; Saeed reza Hosseinzadeh; Mehdi Rejeh (پژوهش‌های حبوبات ایران, 2017)
Introduction Lentil (Lens culinaris Medik.) is a good source of protein, carbohydrates as well as minerals, vitamins and unsaturated fatty acids as such it plays an important role in the human diet and cultivated worldwide. Water shortage is one of the most important abiotic factors that can limit morphological, physiological, yield, and plant distribution. Legumes such as lentil are highly sensitive to water stress. According to references, increasing the concentration of CO2 can neutralize the effects of water stress on plants. One of the ways for increasing the concentration of CO2 in plants is using compounds such as methanol, ethanol, propanol, butanol, and the glycine amino acids, glutamate and aspartate. Methanol is oxidized to formaldehyde and CO2, and further synthesized into sugars and amino acids, including serine and methionine, in tissues of various C3 plants. In plants, methanol can arise from a number of sources; for example, from pectin de-methylation in cell walls, protein repair pathways and lignin degradation. Metabolism of methanol is less understood in plants. The identity of enzymes that oxidize methanol to formate in plants is unclear yet. However, positive growth effects of methanol have been reported earlier in a variety of C3 plants like wheat, barley, mung bean, chickpea, bean, tomato and cotton. Research has shown that plants respond to water deficit stress by accumulations of soluble materials in cells. Most compatible compounds contain soluble proteins, sorbitol, organic acids, proline content and ions such as K and Ca. K deficiency in plants leads to reduced Rubisco activity, stomatal conductance and an increase of reactive oxygen species (ROS), which ultimately reduces photosynthesis. As water stress is one of the major problems for production in the agricultural in Iran. The aims of this study were to determine: (1) whether foliar application of methanol can be improve the negative effects of water deficit stress in lentil and (2) determine the most effective methanol concentration for foliar application.